Monoclonal Antibody-Directed Therapy - Kayser, Veysel; Datta-Mannan, Amita (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book deals with therapeutic monoclonal antibodies (mAbs) broadly, and relevant topics such as challenges and opportunities, next-generation antibody products, Antibody-Drug-Conjugates (ADC), bispecifics, glycosylation, and T-cell engagers are covered. Each topic has been written by leading groups around the world and the book should be of interest to researchers from both academia and industry.